Exploring the potential of Desmodium gangeticum (L.) DC. extract against spatial memory deficit in rats - Changdar, Nilanjan; Ganjhu, Rajesh Kumar; Rijal, Samita; Kumar, Ayush; Mallik, Shanchari Basu; Nampoothiri, Madhavan; Shenoy, Rekha R.; Sonawane, Kiran B.; Rao, Mallikarjuna C.; Mudgal, Jayesh (Pharmacognosy Magazine, 2019)
Background: A few published reports demonstrated the neuroprotective effect of Desmodium gangeticum (L.) DC. in an acute model of dementia. Objective: The purpose of the present study was to evaluate the preclinical efficacy of D. gangeticum against chronic dementia when administered prophylactically. Materials and Methods: Chronic spatial memory deficit was induced in rats by aluminum chloride (AlCl3, 10 mg/kg, i.p.). Treatment with hydroalcoholic whole plant extract of D. gangeticum (DG extract) was initiated 2 week before AlCl3 challenge and continued till the 51(st) day after the challenge, orally at the dose of 400 mg/kg/day. The spatial memory was assessed by Morris water maze test. Hippocampal and frontal cortex acetyl cholinesterase (AChE) and oxidative stress were assessed in diseased rat brains. Results: Chronic administration of AlCl3 produced spatial memory deficit in rats. Memory impairment was manifested in rats as an increase in escape latency and D-quadrant latency whereas a decrease in total time spent in D-quadrant. These behavioral alterations were reversed significantly by the treatment with DG extract. In addition, DG extract significantly increased the island time, indicating memory improvement. DG extract corrected the declined AChE in frontal cortex and altered frontal cortex/hippocampus catalase activity. Phytochemical investigation of the DG extract revealed large content of saponins among the other phytochemicals such as tannins, alkaloids, and flavonoids. Conclusion: These results indicate the possible prophylactic potential of saponin-rich DG extract against chronic memory deficit in rats.
Keywords: Acetyl cholinesterase; Aluminum chloride; dementia; Desmodium gangeticum (L) DC; Oxidative stress